"c_1v_1+c_2v_2+c_3v_3+c_4v_4=0"
"c_1(1, 0, 0)+c_2(1, 1, 0)+c_3(3, 1, 0)+c_4(0, -2, 0)=0"
From the above equation we get the following equations:
"c_1+c_2+3c_3=0"
"c_2+c_3-2c_4=0"
Simplifying we get:
"c_1=2c_3-2c_4"
"c_2=2c_4-c_3"
The {"v_1,v_2" } spans span of subspace and are linearly independent.
Indeed,
"c_1v_1+c_2v_2=0," "c_1(1,0,0)+c_2(1,1,0)=0."
We obtain the following equations
"c_1+c_2=0,"
"c_2=0."
Hence "c_2=0, c_1=0."
Thus, {"v_1,v_2" } is the basis.
Checking option (A)
"v_3=2v_1+v_2," "v_4=2v_1-2v_2."
Thus, "v_1" and "v_2" form a basis for span "\\{ v_1, v_2, v_3, v_4 \\}."
Comments
Leave a comment